2023
DOI: 10.7554/elife.85727
|View full text |Cite
|
Sign up to set email alerts
|

A TRAF-like E3 ubiquitin ligase TrafE coordinates ESCRT and autophagy in endolysosomal damage response and cell-autonomous immunity to Mycobacterium marinum

Abstract: Cells are perpetually challenged by pathogens, protein aggregates or chemicals, that induce plasma membrane or endolysosomal compartments damage. This severe stress is recognised and controlled by the endosomal sorting complex required for transport (ESCRT) and the autophagy machineries, which are recruited to damaged membranes to either repair or to remove membrane remnants. Yet, insight is limited about how damage is sensed and which effectors lead to extensive tagging of the damaged organelles with signals,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 94 publications
1
4
0
Order By: Relevance
“…3, 5 and 8). These data are consistent with and extend the finding that Dictyostelium Vps32 is required for autophagosome maturation 57 , and provide a mechanism by which disruption of autophagy impairs development in Dictyostelium by reducing secretion of c-di-GMP. Most astonishingly, we found that the regulatory Prp4k- vps32 splicing circuit is evolutionarily conserved in humans, where mis-splicing of CHMP4B after PRP4K depletion (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…3, 5 and 8). These data are consistent with and extend the finding that Dictyostelium Vps32 is required for autophagosome maturation 57 , and provide a mechanism by which disruption of autophagy impairs development in Dictyostelium by reducing secretion of c-di-GMP. Most astonishingly, we found that the regulatory Prp4k- vps32 splicing circuit is evolutionarily conserved in humans, where mis-splicing of CHMP4B after PRP4K depletion (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Previous work combined with the current study, implicates PRP4K in a cluster of cellular functions that are seemingly unrelated, including endocytic trafficking 22 , mitosis/cytokinesis 23,34 , and autophagy in human cells and Dictyostelium. However, these represent a very similar cluster of pathways known to be regulated by ESCRT machinery, including endocytic trafficking, cell abscission and autophagy [54][55][56][57][58] . Given this similarity, we hypothesized that expression of ESCRT genes may be affected by the loss of PRP4K.…”
Section: Chmp4b Is Mis-spliced With Prp4k Knockdownmentioning
confidence: 99%
“…Dictyostelium discoideum Ax2(Ka) wild-type cells were grown in axenic conditions at 22 °C in HL5c medium (Formedium) including glucose supplemented with vitamins and micro-elements, as described previously [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…1A ) ( 3 , 22 , 23 ). D. discoideum has emerged as a powerful genetically and biochemically tractable model to study processes of M. marinum infection, and in particular has recently been used to demonstrate the role of the ESCRT and autophagy machinery in MCV membrane repair ( 24 , 25 ), the role of metal poisoning in bacterial growth restriction ( 26 , 27 ) as well as to identify anti-infective compounds ( 28 , 29 ). Therefore, we use D. discoideum and M. marinum as a model system to study cell-autonomous defense mechanisms that are relevant to the pathogenesis of tuberculosis ( 3 , 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%